Analysis of Students' Critical Thinking Ability Based on Sense of Belonging to Mathematics - Endang Retno Winarti; Kartono Kartono; Wardono Wardono; Masrukan Masrukan (Universitas Negeri Semarang, 2021)
This study aims to analyze students' critical thinking ability in introduction to number theory courses based on their sense of belonging mathematics. The learning model used is the Issue Rule Application with online Collaborative Assessment. Critical thinking ability are needed in learning mathematics, especially in introduction to number theory courses. Make grow a sense of belonging to mathematics is fundamental in educational research, regardless of other factors. Online learning certainly provides flexible learning opportunities but comes with important issues in the current pandemic. For online learners, maintaining a sense of belonging to mathematics can provide a way to enhance learning experiences and achievements. This research is a qualitative or naturalistic research because it is carried out in natural conditions that produce descriptive data. Interviews were conducted on 6 students after collecting data on critical thinking skills using a test and sense of belonging mathematics using a questionnaire. The results showed that students with a high sense of belonging to mathematics did not always have high critical thinking skills, students with moderate sense of belonging to mathematics had moderate critical thinking skills, students with low sense of belonging to mathematics had low critical thinking skills and some had low sense of belonging to mathematics. Also high. This happens because students in the first semester still need to develop a sense of belonging in mathematics by providing continuous motivation, optimizing interaction/involvement in learning, and having a fun learning culture.